2015
DOI: 10.1515/biol-2015-0027
|View full text |Cite
|
Sign up to set email alerts
|

Free radical-scavenging activity of sequential leaf extracts of Embothrium coccineum

Abstract: The aim of this study was to evaluate the influence of phenolic, flavonoid, and anthraquinones from sequential extracts (n-hexane, dichloromethane, ethyl acetate, and ethanol) of Embothrium coccineum leaves on the antioxidant capacity, cell viability, and toxicity of the same, in order to find possible sources for novel antioxidants for food and pharmaceutical formulations. Antioxidant potential of sequential extracts was analyzed by five different assays: 2,2-diphenyl-1- picrylhydrazyl radical scavenging acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The H 2 O 2 scavenging activity was determined according to a previously described method [ 57 ]. A solution of hydrogen peroxide (40 mM) was prepared in phosphate buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 O 2 scavenging activity was determined according to a previously described method [ 57 ]. A solution of hydrogen peroxide (40 mM) was prepared in phosphate buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…The TRAP of the essential oil was determined by ABTS + (2,2′-azinobi(3-ethylbenzothiazoline-6-sulfonic acid)) assay [ 57 ]. The ABTS + (2,2′-azinobi(3-ethylbenzothiazoline-6-sulfonic acid)) radical solution (150 µM) was mixed with 2,2′-azo-bis(2-amidino propane) (ABAP) solution (10 mM) in phosphate-buffered saline (PBS), pH 7.4 solution (100 mM).…”
Section: Methodsmentioning
confidence: 99%
“…A previous study showed that the chemical components of E. coccineum include anthraquinones, flavonoids and phenols [6]. It is known that secondary metabolites such as those described in E. coccineum have good antimicrobial properties.…”
Section: Resultsmentioning
confidence: 99%
“…The aerial parts of E. coccineum have been used as a folk remedy for the treatment of neuralgia, tooth pains, wound healing, and glandular conditions, as well as an antiseptic agent in various cultures, for example among the Aónikenk, Huilliche, Kawésqar and Yagan people [3,4]. An earlier study by Mølgaard suggested that the ethanol extract of E. coccineum does not exhibit significant antibacterial activity against E. coli and P. aeruginosa [5], while in other studies it has been shown that extracts of E. coccineum have antioxidant activity because of their contents of phenols, flavonoids and anthraquinones, and molecules which were related to antimicrobial activity [6]. However, the available information concerning E. coccineum is particularly limited.…”
Section: Introductionmentioning
confidence: 99%
“…The DPPH assay was performed as described previously [ 89 ]. Briefly, 0.1 mL sample (from 0 to 4 mg/L of flower extracts) was mixed with 2.9 mL DPPH● solution (50 μM) and such a solution was freshly prepared in ethanol.…”
Section: Methodsmentioning
confidence: 99%